Sierpinski carpet fractal antenna with circular shaped defected ground structure (DGS) / Mohamad Fadhli Rahim - Rahim, Mohamad Fadhli (2014)
This work presents the design, simulation and fabrication of a Sierpinski carpet fractal antenna with circular shaped ground structure (DGS). The proposed antenna was designed and simulated at the centre frequency of 5.8 GHz and fabricated on roger RT/Duroid 5880 substrate with relative permittivity of 2.2 susbtrate thickness of 0.381 mm and copper thickness of 0.017mm.